The fountainhead - Rand, Ayn.; Hurt, Christopher, 1959- ([Ashland, OR] : Blackstone Audio, 2007)
The story of an intransigent young architect, Howard Roark, of his violent battle against a mindless status quo, and of his explosive love affair with a beautiful woman who worships him yet struggles to defeat him. In order to build his kind of buildings according to his own standards, Roark must fight against every variant of human corruption.
Tracks every 3 minutes.
Unabridged.
Read by Christopher Hurt.
Compact discs.
Keywords: Architects -- Fiction; Individualism -- Fiction; Audiobooks; Psychological fiction; Didactic fiction; Love stories